Adaptation of an instrument to classify neonatal patients into care categories - Ariane Polidoro Dini; Andrezza de Cassia Vannucci de Oliveira; Beatriz Pera de Almeida-Hamasaki; Norma Mejias Quinteiro; Elenice Valentim Carmona (SciELO, 2021)
ABSTRACT Objective: To adapt and validate a patient classification instrument for neonatal units. Method: Methodological study, with adaptation of the Pediatric Patients Classification Instrument for neonatal patients. After content validation by judges, the instrument was tested for reliability, applied to 33 neonates by two nurses, simultaneously. To assess the agreement among nurses regarding the scores of each patient on the classification scale, an intraclass agreement coefficient was applied. To assess the agreement regarding the classification in care categories, the weighted Kappa coefficient was calculated. Results: The adapted instrument consisted of a total of nine indicators, with three care categories: high dependence on care, semi-intensive care and intensive care. The Content Validity Index varied between 0.85 and 0.92 for items of the instrument. The intraclass agreement was 0.87 and the weighted Kappa for care categories was 0.56. Conclusion: An instrument that allows neonatal patients to be classified into care categories, with satisfactory reliability was validated to support the dimensioning of the nursing team.